Estimates for Commutators of Bilinear Fractional p-Adic Hardy Operator on Herz-Type Spaces. (4th February 2021) - Hussain, Amjad; Sarfraz, Naqash; Khan, Ilyas; Alqahtani, Aisha M.
Abstract : In the current article, we investigate the boundedness of commutators of the bilinear fractional p -adic Hardy operator on p -adic Herz spaces and p -adic Morrey-Herz spaces by considering the symbol function from central bounded mean oscillations and Lipschitz spaces.